2021
DOI: 10.1186/s12879-021-06971-2
|View full text |Cite
|
Sign up to set email alerts
|

Immature granulocyte percentage for prediction of sepsis in severe burn patients: a machine leaning-based approach

Abstract: Background Of the existing sepsis markers, immature granulocytes (IG) most frequently reflect the presence of an infection. The importance of IG as an early predictor of sepsis and bacteremia is evaluated differently for each study. This study aimed to evaluate the effectiveness of the Sysmex XN series’ IG% as an independent prognostic indicator of sepsis using machine learning. Methods A total of 2465 IG% results from 117 severe burn patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These unassigned cells may represent known cell types altered significantly under sepsis, making them unrecognizable by conventional markers, or they may be a novel subtype of immune cells that emerge in response to sepsis. Furthermore, the unassigned cells could be immature granulocytes, given that sepsis is known to induce the recruitment of immature neutrophils into the bloodstream. The presence of these unassigned cells could indicate a potentially unexplored mechanism of immune response modulation in sepsis, suggesting that further research into their identity is crucial to uncovering new facets of immune system behavior in response to severe infection and systemic inflammation. The unassigned cells observed in this study require more thorough exploration, and we emphasize the need for further research to expand our understanding of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…These unassigned cells may represent known cell types altered significantly under sepsis, making them unrecognizable by conventional markers, or they may be a novel subtype of immune cells that emerge in response to sepsis. Furthermore, the unassigned cells could be immature granulocytes, given that sepsis is known to induce the recruitment of immature neutrophils into the bloodstream. The presence of these unassigned cells could indicate a potentially unexplored mechanism of immune response modulation in sepsis, suggesting that further research into their identity is crucial to uncovering new facets of immune system behavior in response to severe infection and systemic inflammation. The unassigned cells observed in this study require more thorough exploration, and we emphasize the need for further research to expand our understanding of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the association between immature granulocyte counts (IG# and IG%) and blood culture positivity in pediatric patients with cardiac disease [14,15]. In a study published in the Journal of Clinical Laboratory Analysis in 2018, it was observed that patients with positive blood cultures exhibited significantly higher immature granulocyte counts (IG# and IG%) compared to those with negative blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on patients with sepsis in 2019, Ayres et al [11] found the IG percentage was significant in demonstrating sepsis. Jeon et al [12] found that the percentage of IG was moderately significant in demonstrating sepsis in patients who developed sepsis after burns in 2021. Karon et al [13] in 2017, found that the percentage of IG was moderately significant in showing sepsis in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%